Effects of vegetation structure and human impact on understory honey plant richness: Implications for pollinator visitation - Cho, Y.; Lee, D.; Bae, S.
Though the biomass of floral vegetation in understory plant communities in a forested ecosystem only accounts for less than 1 percent of the total biomass of a forest, they contain most of the floral resources of a forest. The diversity of understory honey plants determines visitation rate of pollinators such as honey bee (Apis mellifera)as they provide rich food resources. Since the flower visitation and foraging activity of pollinators lead to the provision of pollination service, it also means the enhancement of plant-pollinator relationship. Therefore, an appropriate management scheme for understory vegetation is essential in order to conserve pollinator population that is decreasing due to habitat destruction and disease infection. This research examined the diversity of understory honey plant and studied how it is related to environmental variables such as (1)canopy density, (2)horizontal heterogeneity of canopy surface height, (3)slope gradient, and (4)distance from roads. Vegetation survey data of 39 plots of mixed forests in Chuncheon, Korea, were used, and possible management practices for understory vegetation were suggested. Results: This study found that 113 species among 141 species of honey plant of the forests were classified as understory vegetation. Also, the understory honey plant diversity is significantly positively correlated with distance from the nearest road and horizontal heterogeneity of canopy surface height and negatively correlated with canopy density. Conclusions: The diversity of understory honey plant vegetation is correlated to vegetation structure and human impact. In order to enhance the diversity of understory honey plant, management of density and height of canopy is necessary. This study suggests that improved diversity of canopy cover through thinning of overstory vegetation can increase the diversity of understory honey plant species.
Keywords: AIRBORNE LIDAR; APIS MELLIFERA; FOREST ECOLOGY; POLLINATION SERVICE; VEGETATION STRUCTURE